Psychosocial well-being and quality of life in women with Turner syndrome. (March 2020) - Liedmeier, Ariane; Jendryczko, David; van der Grinten, Hedi Claahsen; Rapp, Marion; Thyen, Ute; Pienkowski, Catherine; Hinz, Andreas; Reisch, Nicole
Highlights: women with Turner syndrome suffer from impairment in all quality of life domains and experience psychosocial challenges. Depression and self-esteem seem to be the best predictors of quality of life in women with Turner syndrome. Women with Turner syndrome are satisfied with their work life and income. Abstract: Background: Turner syndrome (TS) affects approximately one out of 2500 females. Previous research indicates that women with TS experience impairment in several psychosocial domains as well as in quality of life (QoL). Data, however, mainly focus on girls, whereas data on adult women is extremely scarce, inconsistent and mainly low in sample size. Separate analysis of adult women, however, is important since women face other challenges of TS than girls. Methods: We compared 301 women with TS aged 16–73 years (from 14 centres in six European countries) to healthy controls with regard to depression, anxiety, self-esteem, attention deficit/hyperactivity disorder (ADHD), autism, romantic relationships, social participation, amount of working hours and satisfaction with income as well as with regard to psychological, physical, environmental, social and global QoL. The influence of psychosocial well-being on the different QoL-domains was examined via multiple regression models. Results: Women with TS showed impairments in all psychosocial variables (anxiety, depression, ADHD, autism, self-esteem, social participation all p  <  0.001) except for the amount of working hours ( p  =  0.062) and satisfaction with income ( p  =  0.369). They also showed lower social ( p  <  0.001), psychological ( p  <  0.001) and physical QoL ( p  <  0.001) compared to controls. Depression, satisfaction with income and self-esteem could be shown to be the best predictors for QoL. Conclusion: In conclusion, quality of life in TS is impaired, in particular it seems to be negatively affected by depression and low self-esteem whereas satisfaction with income has a positive influence. These results implicate that medical staff needs to pay attention on possible psychosocial impairments when treating women with TS. Strengthening self-esteem and counteracting depression potentially raises their QoL.